Contra Legem as a Solution in Resolving Gono-Gini Property Disputes in Religious Courts - Dewi Anggraini; Nurul Hikmah (Indonesian Journal of Islamic Law, 2020)
This research examines the application of the Contra Legem concept in resolving gono-gini property disputes in the Religious Courts. The main focus of this research is to evaluate the effectiveness of applying this concept in achieving substantive justice and increasing public trust in the religious justice system. Empirical data shows that judges who apply the Contra Legem concept succeed in reaching decisions that are fairer and more satisfying for the parties to the dispute. The theoretical support of the principles of ijtihad and maqasid al-shariah strengthens the relevance and effectiveness of these concepts in the context of modern Islamic law. This research also identifies the challenges faced in implementing this concept and provides recommendations for improving education and training for judges so that Islamic law can continue to develop and be responsive to social dynamics.